Reliability engineering : methods and applications - Ram, Mangey (Boca Raton : CRC Press, 2019)
"Over the last 50 years, the theory and the methods of reliability analysis have developed significantly. Therefore, it is very important to the reliability specialist to be informed of each reliability measure. This book will provide historical developments, current advancements, applications, numerous examples, and many case studies to bring the reader up-to-date with the advancements in this area. It covers reliability engineering in different branches, includes applications to reliability engineering practice, provides numerous examples to illustrate the theoretical results, and offers case studies along with real-world examples. This book is useful to engineering students, research scientist, and practitioners working in the field of reliability"--
Chapter 13: Reliability Assessment and Probabilistic Data Analysis of Vehicle Components and SystemsChapter 14: Maintenance Policy Analysis of a Marine Power Generating Multi-state System; Chapter 15: Vulnerability Discovery and Patch Modeling: State of the Art; Chapter 16: Signature Reliability Evaluations: An Overview of Different Systems; Index
OCLC-licensed vendor bibliographic record.
Keywords: Reliability (Engineering); BUSINESS & ECONOMICS / Quality Control; TECHNOLOGY / Engineering / General; TECHNOLOGY / Engineering / Industrial